Diseño de un sistema semiautomático para lavado de botellas de vidrio tipo III, de 750 ml de capacidad. - Reyes Villavicencio, Alonso Geovanny (2017)
The present work describes the design of a semi - automatic type III glass bottle washing system, of 750 ml, which will be presented as a solution to the cleaning process of glass containers for Vinos y Licores Vilcabamba factory. The bottle washers are designed to clean and disinfect new or recycled containers, in order to obtain an optimum sanitary condition for use in the subsequent packaging of the products. Through the methodology that was used, information was synthesized about technological processes of the different types of glass bottle washing machines available on the market, and a rotating washing machine with a production of approximately 140 bottles / hour was chosen as the best option. The principle of operation of the rotary washing machine is based on subjecting the bottles to a washing process with a specialized treatment of caustic solution, where the quality conditions of the bottles are guaranteed to pack the product. The washing machine will consist of three compartments, each intended to carry out a specific operation of a washing cycle. The first compartment will be used to disinfect the bottles by injecting caustic solution at 71 °C, continuing to the next compartment where the labels removing will be performed by the injection of pressurized water and finally the containers will pass to the last compartment where it will be made the rinse. The present proposed project presents the design of a system for washing glass bottles, establishing necessary considerations to calculate, size and select its main components. In addition the design consists of a proposal of semi-automatic control commanded by a PLC to facilitate the actuation of the various electromechanical elements. For constructive details for the semi-automatic bottle washing system, the respective planes of the constituent elements are presented.